(untitled) (Sir Salimullah Medical College Journal, 2023)
Introduction: Emergency peripartum hysterectomy (EPH) is a life-saving surgical procedure performed when medical and surgical conservative measures fail to control postpartum hemorrhage. EPH is a challanging but life saving obstetric procedure performed when medical and surgical conservative measures fail to control postpartum haemorrhage .The present study aimed to review the peripartum hysterectomies and to compare the incidence, indications and outcome of EPH. Materials and Methods: This retrospective study was conducted at a tertiary care hospital in Dhaka, Bangladesh. Total 62 cases have taken, who had hysterectomy that was performed in Obstetric and gynaecology department of Addin Womens Medical College Hospital during the period between January 2020 and December 2022. Result: There were total of 36371 deliveries over the study period and EPH was performed in 62 cases making an incidence of 0.408. In this study 33.8% patients were between 35 to 39 years. Here 45.16% had their parity between 2nd and 3rd child. Here 61.2% had previous history of caesarean section, 24.19% had previous history of antepartum haemorrhage, 74.19% cases intrapartum operation had done. Among 62 cases of EPH 77.4% cases subtotal hysterectomy had done. Here, among 62 cases of caesarean section 35.48% had placenta accrete and 20.96% had history of placenta previa with haemorrhage and 12.9% had severe PPH due to atony of uterus. 22.5% cases had fetal outcome of still born but 32.25% baby born alive. In this study 51.6% cases patients develop haemorrhage as perioperative complication, 19.5% develop shock but 100% required blood transfusion among which 50% were in post operative period. Here 6 out of 62 cases had bladder injury, 5 patients needed relaparotomy due to haemoperitoneum caused by vaginal cuff bleeding. Mortality rate was 4.83%. Conclusion: Now a days the indication of EPH has changed from uterine atony to abnormal placentation. It is a most important obstetric surgery performed in life threatening haemorrhage. Involvement of an experienced obstetrician at an early stage of management and efforts should be taken to reduce morbidity and mortality. Sir Salimullah Med Coll J 2023; 31: 107-111